2018
DOI: 10.3390/s19010066
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Polyphenol Indices and Antioxidant Capacity for Beers and Wines Using a Tyrosinase-Based Biosensor Prepared by Sinusoidal Current Method

Abstract: The application of a novel Poly(3,4-ethylenedioxythiophene)-Tyrosinase/Sonogel-Carbon electrode (PEDOT-Tyr/SNGC) biosensor to beers and wines analysis is proposed. This biosensor implies a new Sinusoidal Current (SC) electrodeposition method to immobilize the enzyme generating a nanostructure surface. The biosensors were characterized electrochemically, employing cyclic voltammetry and electrochemical impedance spectroscopy. Sensitivity, limit of detection, and correlation coefficients of the linear fitting we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 40 publications
(53 reference statements)
0
37
0
Order By: Relevance
“…The estimated cost for the biosensor was under 2 euros and the fabrication time was under 5 min. No decrease in biosensor performances was observed after storage for 10 days at 4 • C [90].…”
Section: Enzyme-mediated Amperometric Detectionmentioning
confidence: 86%
See 2 more Smart Citations
“…The estimated cost for the biosensor was under 2 euros and the fabrication time was under 5 min. No decrease in biosensor performances was observed after storage for 10 days at 4 • C [90].…”
Section: Enzyme-mediated Amperometric Detectionmentioning
confidence: 86%
“…Application of this biosensor for the analysis of the total polyphenol index in two wine samples (white and red) in 0.1 mol L −1 acetate buffer, pH 4.5 with amperometric detection at −0.1 V has allowed calculating values of the total polyphenol index very close to those determined by the Folin-Ciocalteu method. In one report on tyrosinase based biosensors for wine analysis, the enzyme was immobilized on the surface of sonogel carbon electrodes concomitantly with the electropolymerisation of EDOT (3,4-ethylenedioxythiophene), using a sinusoidal current method [90]. The PEDOT/tyrosinase/sonogel carbon biosensor had a Km app of 178.72 µmol L −1 , showing a high affinity for caffeic acid.…”
Section: Enzyme-mediated Amperometric Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Grapes and wines can exhibit very high antioxidant values, in vitro, allowing the assumption that these foods can serve as very potent antioxidants although less is known about effects in vivo. 12,28,29 Additionally, several studies have shown that the ethanol content combined with the polyphenol content of red wine helps improve and/or maintain endothelial function. 20,[30][31][32] In support of this concept, we found that only the acute red wine consumption resulted in a significant increase in FRAP and a significant decrease in AIx.…”
Section: Discussionmentioning
confidence: 99%
“…For the second assay, an increase in the signal compared with the signal obtained for individual phenols was explained either by the synergic effect among the polyphenols or by the contribution from several not individually detectable polyphenols. The same group improved the biosensor a few years later by adding a polymer film, poly(3,4-ethylenedioxythiophene (PEDOT), into the biosensor architecture and using Lac instead of Tyr [ 38 ]. Another simple approach based on a carbon paste electrode on which Tyr is immobilized in a Nafion film was presented by Sýs et al [ 39 ].…”
Section: Biosensors For the Assessment Of Phenol Classesmentioning
confidence: 99%